Grass Carp: A Fish for Biological Management of Hydrilla and Other Aquatic Weeds in Florida - David L. Sutton; Vernon V. Vandiver, Jr.; Jeffrey E. Hill (EDIS, 2013)
Abundant growth of aquatic plants causes serious problems in ponds, lakes, rivers, and irrigation and drainage throughout Florida. In some situations, native aquatic plants become weeds, but most often exotic plants introduced from areas outside the state flourish under the favorable growing conditions found in Florida. Long-term economical solutions to Florida’s aquatic weed problems have been elusive and there is a need for control techniques to alleviate aquatic weed problems. This 6-page fact sheet provides information on a biological method, the grass carp, for management of some of Florida’s aquatic weed problems. Written by David L. Sutton and Vernon V. Vandiver, Jr., and published by the UF Department of Fisheries and Aquatic Sciences, November 2012.